Investigating Women's Preferences in the Public Spaces of Gated Communities - A Case Study of Atisaz Residential Complex - Sara Anbari; Seyed Abbas Yazdanfar; Seyed Hadi Ghoddusi Far; Azadeh Shahcheraghi (توسعه پایدار شهری)
This study examines the needs and preferences of women in the public spaces of gated communities. Given that the type and extent of outdoor activities in built environments are heavily influenced by physical and spatial planning, exploring the concept of lifestyle as a comprehensive set of functions and realities of people's lives can lead to a better understanding of the needs and desires of residents in spatial planning of residential environments. Considering that women constitute half of the population of any society and are responsible for a significant portion of family functions, taking into account their preferences and needs in shaping residential environments can contribute to their physical, mental health, and overall quality of life. However, research on housing behaviors based on women's lifestyles is rarely examined in the literature. The aim of this study was to identify general needs by discovering individual women's needs. Given that the starting point of this research is the examination of individual needs, autoethnography was chosen as the research method, and thematic analysis was used to organize qualitative data and analyze the text reports. The results, based on the analysis of the presented reports, indicate that women's lifestyles in the public spaces of gated communities are multifaceted and can be identified in relation to self, others, the natural environment, the built environment, and personal scheduling. These themes describe the requirements and preferences based on lifestyle and indicate that some requirements are more general, while others include unique women's needs that must be considered in the design and implementation of future residential environments.